Promoting Holistic Development - Khamis, Ukhanna Mirza; Hamza, Saddam Hammo (Journal of Tikrit University for Humanities, 2024)
The research is based on two parts. The first is theoretical, in which we explained the meaning of the term grammatical calcification, by which we mean the closeness of grammatical topics to each other to the point that parsers confuse grammatical topics, which we called calcification, such as confusion between types of exception, between adverb and distinction, and between declarative conjunctions. This calcification kept us from knowing the real difference between these topics, but through the three aforementioned elements in grammatical analysis, we arrive at the difference between the grammatical topics, and at the same time reduces the disagreement between the parsers regarding the calcified topics. The second part of the research is a study on the characteristics of functions through their boundaries, and an explanation of the areas of grammatical calcification in them.